Analysis of Difference of Knowledge, Perceptions, and Willingness to Adopt Islamic Banking Services (a case study in FEBI IAIN Gorontalo) - Fadhilah, Nurul; Nur, Rahmawati; Sintiawati, Rini (Universitas Siliwangi, 2024)
Introduction to the problem: Gorontalo is a Muslim-majority province. However, the growth of Islamic banking is not so significant compared to the number of potential customers. This is due to the lack of understanding of Islamic banking product and service.Purpose/Objective of the study: This research attempted to identify the role of universities in shaping knowledge, perceptions, and willingness to use Islamic bank products and services. Design/Methodology: This research was conducted at FEBI IAIN Sultan Amai Gorontalo. Questionnaire are distributed to identify the knowledge, perceptions, and the willingness to adopt Islamic banking product and services. The samples are divided into two groups of students. Group A are the 1st and 2nd year students, Group B are 3rd and 4th year students based on the completion of the Islamic banking courses. Findings: This study identified that there is no difference between the first and second-year student groups, with the third- and fourth-year students of the level of knowledge, perception, and willingness to adopt Islamic banks. However, the results show the role of the university in providing the student awareness in Islamic banking through the knowledge, perspectives, and the willingness to use Islamic banking. In addition, several recommendations are assisted to intensify the role universities to support the industry.